Reionization time of the Local Group and Local-Group-like halo pairs - Sorce, Jenny; Ocvirk, Pierre; Aubert, Dominique; Gottlöber, Stefan; Shapiro, Paul R; Dawoodbhoy, Taha; Yepes, Gustavo; Ahn, Kyungjin; Iliev, Ilian T; Lewis, Joseph (Monthly notices of the Royal Astronomical Society, 2022)
Patchy cosmic reionization resulted in the ionizing UV background asynchronous rise across the Universe. The latter might have left imprints visible in present-day observations. Several numerical simulation-based studies show correlations between the reionization time and overdensities and object masses today. To remove the mass from the study, as it may not be the sole important parameter, this paper focuses solely on the properties of paired haloes within the same mass range as the Milky Way. For this purpose, it uses CoDaII, a fully coupled radiation hydrodynamics reionization simulation of the local Universe. This simulation holds a halo pair representing the Local Group, in addition to other pairs, sharing similar mass, mass ratio, distance separation, and isolation criteria but in other environments, alongside isolated haloes within the same mass range. Investigations of the paired halo reionization histories reveal a wide diversity although always inside-out, given our reionization model. Within this model, haloes in a close pair tend to be reionized at the same time but being in a pair does not bring to an earlier time their mean reionization. The only significant trend is found between the total energy at z = 0 of the pairs and their mean reionization time: Pairs with the smallest total energy (bound) are reionized up to 50 Myr earlier than others (unbound). Above all, this study reveals the variety of reionization histories undergone by halo pairs similar to the Local Group, that of the Local Group being far from an average one. In our model, its reionization time is ∼625 Myr against 660 ± 4 Myr (z ∼ 8.25 against 7.87 ± 0.02) on average.
Gesehen am 25.09.2022